Design and Construction of a Mathematical Pendulum Harmonic Motion Experiment System Using Arduino Based E18-D80Nk Proximity Sensor - Mulyadi, Endri; Asrizal, Asrizal; Amir, Harman; Sari, Mona Berlian (Journal of Experimental and Applied Physics, 2024)
Experimentation is part of the stages of the scientific method that has a big role to test a phenomenon that occurs. One of the physics lessons proven through experiments is the harmonic motion of a mathematical pendulum. One of the problems with the existing experimental equipment is the variation in rope length and the manual measurement of rope length. One solution to overcome this problem is to create a Mathematical Pendulum Harmonic Motion Experiment System Using the Arduino-based E18-D80NK Proximity Sensor. This tool is designed to facilitate practitioners when conducting experiments and save practicum time. Research was conducted to determine the accuracy and precision of the tool. The experimental results of the device can be displayed on the LCD.  The precision and accuracy of the experimental system with the following details: Average error of 0.65% for comparison of system t value and standard t and average error of 0.55% for comparison of system gravitational acceleration value with theoretical gravitational acceleration for variation of rope length. As for the average value of accuracy of 0.9990583 or 99.9% for a fixed rope length, and the average accuracy of 0.99793367 or 99.7% for a fixed number of oscillations.